2011
DOI: 10.1063/1.3505797
|View full text |Cite
|
Sign up to set email alerts
|

Pressure cell for investigations of solid–liquid interfaces by neutron reflectivity

Abstract: We describe an apparatus for measuring scattering length density and structure of molecular layers at planar solid-liquid interfaces under high hydrostatic pressure conditions. The device is designed for in situ characterizations utilizing neutron reflectometry in the pressure range 0.1-100 MPa at temperatures between 5 and 60 °C. The pressure cell is constructed such that stratified molecular layers on crystalline substrates of silicon, quartz, or sapphire with a surface area of 28 cm(2) can be investigated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 21 publications
2
18
0
Order By: Relevance
“…in the gel state ß ′ ), the thickness of the water interlayer including the adjacent headgroups of membrane and + 1 reads as 32.1 Å. 31 The water interlayer 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 can be further subdivided into heads / water / heads slices with dimensions of approximately 10 / 10 / 10 Å with small adjustment on the thickness of lipid tails slab from 32.4 to 34 Å. 29 Upon interaction with HA the water interlayer increases drastically from 10  142 Å with additional HA ad-layers, 22 Å in thickness, each with a volume fraction of = 0.23, decorating the lipid headgroups from the aqueous side.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…in the gel state ß ′ ), the thickness of the water interlayer including the adjacent headgroups of membrane and + 1 reads as 32.1 Å. 31 The water interlayer 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 can be further subdivided into heads / water / heads slices with dimensions of approximately 10 / 10 / 10 Å with small adjustment on the thickness of lipid tails slab from 32.4 to 34 Å. 29 Upon interaction with HA the water interlayer increases drastically from 10  142 Å with additional HA ad-layers, 22 Å in thickness, each with a volume fraction of = 0.23, decorating the lipid headgroups from the aqueous side.…”
Section: Discussionmentioning
confidence: 99%
“…3). 31 In all systems the underlying repeat unit consists of one bilayer membrane and one adjacent interlamellar (interstitial) water layer. The thickness of the hydrophobic tails slab of such an aligned DMPC membrane measures 32.4 Å at 21°C (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the design of a HP sample cell for NR bears several challenges, which may explain that only recently first HP sample cells for NR have been reported that allow for lipid and polymer film studies under pressures up to a maximum of 1 kbar. 22,23 In this paper we present a new HP cell for NR experiments. The main features of this cell are a high accessible pressure range up to 2500 bar and a low required volume of sample solution, which is neatly separated from the pressure transmitting medium, water, and from the inner walls of the pressurized equipment.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, neutrons are very penetrating, enabling the use of neutron-transparent windows. Hence, NR can be used to probe challenging systems in situ, including buried interfaces (under liquids) with samples under extreme conditions of temperature andpressure [36][37][38] and under external fields such as shear [39,40] and/or electrochemical potential [41][42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%